Management of health service waste in sentinel units for COVD-19 and the risks to the multiprofissional team and environment (Research, Society and Development, 2023)
This research aimed to describe the management of health care waste (RSS), regarding the segregation stage, in Sentinel Units for COVID-19 in the Municipality of Rondonópolis, State of Mato Grosso, Brazil, and the risks of contamination for the multidisciplinary team and for the environment. This is a quantitative, field and descriptive study, carried out with 69 professionals who were working in the Sentinel Units in relation to the manipulation of RSS from the assistance to patients suspected or contaminated by COVID-19. The data were organized in electronic spreadsheets of the Microsoft Office Excel® program, using descriptive statistics. As for aspects of safety at work, of the 69 participants, 43 (62.31%) stated that they had not received any training; regarding the existence or not of a Health Waste Management Plan (PGRSS), 59 (85.50%) reported that it did not exist; and regarding the perception of professionals about the risks of contamination by handling waste infected by the Coronavirus, 38 (55.07%) reported a correct perception, pointing to high risk; however, 31 (44.92%) reported an incorrect perception of this risk. As for the management of RSS related to the disposal of Personal Protective Equipment (PPE), 44 (63.76%) indicated it incorrectly. It is concluded that there is a commitment to the occupational safety of the professionals involved and the preservation of the environment in relation to the management of RSS, as well as a failure on the part of municipal managers regarding training and supervision.